2000
DOI: 10.1088/0953-4075/33/12/306
|View full text |Cite
|
Sign up to set email alerts
|

T-matrix theory of positron annihilation on hydrogen

Abstract: The transition amplitude for electron-positron annihilation during positron-hydrogen scattering is formulated in terms of the half-shell T-matrix elements obtained from a solution of the momentum space Lippmann-Schwinger equation. The derived expression is well defined at energies below the positronium (Ps) formation threshold. However, singularities in the transition amplitude exist at energies above the Ps-formation threshold. The annihilation parameter for positron-hydrogen scattering is computed in a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 46 publications
(73 reference statements)
5
33
0
2
Order By: Relevance
“…The present Z eff agrees well with those by Van Reeth and Humberston [4] and by Ryzhikh and Mitroy [5] within 5%. The work of Laricchia and Wilkin [3] has been critically assessed earlier [5,7], and no further comment is due here. The result obtained by Yamanaka and Kino [6], using a timedependent version of Eq.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The present Z eff agrees well with those by Van Reeth and Humberston [4] and by Ryzhikh and Mitroy [5] within 5%. The work of Laricchia and Wilkin [3] has been critically assessed earlier [5,7], and no further comment is due here. The result obtained by Yamanaka and Kino [6], using a timedependent version of Eq.…”
supporting
confidence: 92%
“…detailed variational calculations for the e H collisions, though their results are grossly different from the Laricchia-Wilkin model. Ryzhikh and Mitroy [5] found that Eq. (1) they calculated using the momentum-space Lippmann-Schwinger equation lies within a few % difference from the result of Ref.…”
mentioning
confidence: 99%
“…Besides reproducing the low-energy elastic cross section, this model potential approach also does a reasonable job of reproducing Z eff (v). The annihilation parameter is computed from the scattering wave function using [4,25,26] …”
Section: Collision Modelmentioning
confidence: 99%
“…The annihilation parameter Z eff is computed from the scattering wave function using the identity [23][24][25],…”
Section: G Positron Annihilationmentioning
confidence: 99%